JAK inhibitors dampen activation of interferon-stimulated transcription of ACE2 isoforms in human airway epithelial cells - Hye Kyung Lee; Olive Jung; Lothar Hennighausen (Communications Biology, 2021)
Hye Kyung Lee et al. identify additional candidate enhancers linked to the ACE2 promoters producing biologically active ACE2, the receptor for SARS-CoV-2. They also demonstrate JAK inhibitors suppress the interferon-induced genetic programs, including ACE2 expression, in human airway epithelial cells.